#### Answer

$\frac{4}{11}$

#### Work Step by Step

-$\frac{2}{3}$$\times$ -$\frac{6}{11}$= The product of two negative numbers is a positive number
=$\frac{2\times6}{3\times11}$=$\frac{2\times2\times3}{3\times11}$=
=$\frac{4}{11}$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

$\frac{4}{11}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.